RAJA AMPAT DALAM PERSIMPANGAN: DILEMA PEMBANGUNAN BERBASIS TAMBANG DAN PARIWISATA BERKELANJUTAN - Petrus Atong (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Raja Ampat, known as the world's ecotourism paradise for its rich marine biodiversity, now faces a major dilemma between nickel mining exploitation and the preservation of sustainable tourism. On one hand, the increasing global demand for nickel makes this region a target for the expansion of the mining industry. On the other hand, the tourism sector has proven to make a significant contribution to local revenue and the well-being of the local community. This research aims to analyze the tension between these two development interests, as well as their impact on the environment and indigenous communities. Using a qualitative descriptive method with a literature study approach, the study results show that mining activities have a negative impact on the marine ecosystem, customary laws such as "sasi," and the local social structure. Conversely, sustainable tourism can promote environmental conservation while providing long-term economic benefits. However, tourism also brings its own challenges, such as coral reef degradation due to tourist activities and a lack of regulation for managing visits. Therefore, strengthening conservation policies, engaging indigenous communities, and rejecting mining are strategic steps in maintaining the ecological and developmental balance of Raja Ampat.